Framing Sálvame: Public debates on taste, quality and television in Spain - Besalú, Reinald and Oliva, Mercè and Pérez-Latorre, Óliver (Communications, 2018)
Abstract The main aim of this article is to analyze the social circulation of discourses on non-hegemonic cultural practices, in particular, on what is called “trash TV”, and how they are connected to struggles over cultural and social hierarchies. To do so, it takes a specific event as starting point: the injunction that the CNMC (the Spanish broadcasting regulatory body) filed against Mediaset (a commercial TV operator) to adjust the contents of Sálvame Diario (a celebrity gossip program frequently associated with “trash TV”) to the requirements of what is known as the “child protection time slot”. This paper uses constructionist framing to analyze how this event was discussed by different social actors. Our analysis shows that while the CNMC and the press painted the conflict as a legal issue, Sálvame and social media users focused their discussion on the social acceptability of celebrity gossip media and their viewers (specifically working-class women).
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTUxNS9jb21tdW4tMjAxNy0wMDU1